Comparison of adolescents’ Satisfaction with professional Care in Pediatric versus adult wards in Isfahan - sadeghi, Narges; Abdeyazdan, Zahra; Rahmany, Azam; Abdeyazdan, Gholamhosein; Behshti, Shahnaz (Advances in Nursing & Midwifery, 2013)
Abstract Background and aim: Adolescence is a unique physical, cognitive, and psychosocial development period. Adolescent hospitalization could lead to many adverse effects on adolescent and causes problems in all areas. Lack of understanding of adolescents needs could impact on providing care. The aim of this study is to assess adolescents’ satisfaction with professional Care and compare it in two groups of adolescents hospitalized in children and adult wards. Material and Methods: In a cross sectional comparative and descriptive study the satisfaction questionnaires were filled out by 200 adolescents 10- 19 year-old hospitalized in Amin and Alzahra hospitals in Isfahan city. They were selected by convenient sampling method. Data were analyzed by SPSS version 11.5 and via t student ,Mann witney tests and person coefficient. Results: Average satisfaction score with nursing services in teens who hospitalized in pediatric wards was significantly higher than those admitted in the adult’s ward, but there was no statistically significant difference between the two groups in terms of medical and other personnel services. 87 percent of adolescents who were hospitalized in adult’s wards and 35.3 percent of teens who were hospitalized in the children wards preferred to be admitted in the adolescent’s ward. Conclusion: In the present study, satisfaction level of adolescents with nursing services in pediatric ward was higher than those in adult’s ward. Most of adolescent want to hospitalize in adolescents’ ward. So it is suggested if it is not possible to prepare adolescent‘s ward for their care, it is better they hospitalized in children ward . Key Words : patient satisfaction, adolescent, hospitalization, nursing care, hospital, medical care